2008
DOI: 10.1088/1751-8113/41/27/275301
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary fields as a tool for computing analytical solutions of the Schrödinger equation

Abstract: We propose a new method to obtain approximate solutions for the Schrödinger equation with an arbitrary potential that possesses bound states. This method, relying on the auxiliary field technique, allows in many cases to find analytical solutions. It offers a convenient way to study the qualitative features of the energy spectrum of bound states in any potential. In particular, we illustrate our method by solving the case of central potentials with power-law form and with logarithmic form. For these types of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(122 citation statements)
references
References 23 publications
3
119
0
Order By: Relevance
“…Let us note |ν 0 , ρ 0 an eigenstate of the nonrelativistic Hamiltonian H NR given by (7) with ν = ν 0 = p 0 /T ′ (p 0 ) and ρ = ρ 0 = V ′ (r 0 )/(|λ| r λ−1 0 ). Such a state is an approximation of the corresponding eigenstate of H 9 .…”
Section: General Equationmentioning
confidence: 99%
“…Let us note |ν 0 , ρ 0 an eigenstate of the nonrelativistic Hamiltonian H NR given by (7) with ν = ν 0 = p 0 /T ′ (p 0 ) and ρ = ρ 0 = V ′ (r 0 )/(|λ| r λ−1 0 ). Such a state is an approximation of the corresponding eigenstate of H 9 .…”
Section: General Equationmentioning
confidence: 99%
“…, α x 2 + β, … A good accuracy can be obtained with a proper choice of P(x) [1][2][3][4]. Using the comparison theorem [5], it can be shown that E(r 0 ) is an upper (lower) bound of the exact eigenvalues ifṼ (r,…”
Section: The Auxiliary Field Methodsmentioning
confidence: 99%
“…Within this theory, quarks are assumed to be in the fundamental representation of the colour group SU(N c ), with N c → ∞ and the constraint α S N c = α 0 ∼ O (1). Its main feature is the suppression of internal quark loops, provided the number of flavours is finite.…”
Section: An Application For Baryons In the Large-n C Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…To this aim, the auxiliary field technique will be used in order to transform the Hamiltonian (17) into an analytically solvable one [22,23].…”
Section: B General Formulasmentioning
confidence: 99%